Mapping the research landscape of traditional Chinese medicine in insomnia management: a bibliometric study (2005–2024) - Zhang, Chi; Yang, Xiaojie; Ye, Jin; Cai, Yuanxun; Zhang, Hanxiao; Fang, Yuelong; Zhang, Liying; Cai, Shuhe (Frontiers in Neurology, 2025)
ObjectiveTraditional Chinese Medicine (TCM) has shown unique benefits in insomnia management, but existing bibliometric studies on TCM for insomnia remain fragmented. This study, through bibliometric methods, systematically maps the research landscape of TCM in insomnia management from 2005 to 2024, with the objective to explore research hotspots and developmental trends, thereby providing references for future studies.MethodsThis study retrieved English-language literature on the treatment of insomnia with Traditional Chinese Medicine from 2005 to 2024 in the Science Core Collection. The included literature was imported into CiteSpace, VOSviewer, and Bibliometrix R software packages to analyze annual publications, authors, countries/regions, institutions, journals, cited reference, and keywords, in order to explore the hotspots and trends in TCM treatment of insomnia.ResultsA total of 738 articles were included. The number of annual publications in this field increased rapidly from 2016 to 2021. China was the country with the highest number of publications, among which Shanghai University of Traditional Chinese Medicine, Beijing University of Chinese Medicine, and Guangzhou University of Chinese Medicine were the top three institutions in terms of publication volume. Yeung, Wing-fai from Hong Kong Polytechnic University was the author with the highest number of publications. Medicine published 74 articles, the highest number among all journals. Journal of Ethnopharmacology and Sleep were, respectively, the most frequently cited and co-cited journals. The main keywords included sleep, randomized controlled trial, traditional Chinese medicine, acupuncture, etc. The research hotspots mainly focused on acupuncture, chemical components, cancer-related insomnia, and depression-related insomnia. The research focus is transitioning from clinical efficacy to mechanism research, especially the study of the chemical components of traditional Chinese medicine through network pharmacology may be a future research trend. Moreover, this field is paying more attention to insomnia subtypes such as comorbid insomnia and secondary insomnia.ConclusionTCM treatment of insomnia is receiving increasing attention. It shows unique advantages in reducing drug dependence and managing comorbid insomnia. In the future, the evidence-based development of TCM should be promoted through mechanism research, multidisciplinary collaboration, stratified intervention, and the transformation of high-impact evidence, providing an integrated solution for global insomnia management.